2023
DOI: 10.3389/fpls.2022.1066790
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar application of nano-nutrients solution on growth and biochemical attributes of tomato (Solanum lycopersicum) under drought stress

Abstract: IntroductionDrought stress has drastically hampered the growth and yield of many crops. Therefore, environmentally safe agricultural techniques are needed to mitigate drought stress impact. To this end, foliar spray of nano-nutrients solution to (NNS) alleviate harmful aspects of drought stress.MethodsIn a completely randomized design (CRD) experiment, seedlings were transplanted into pots at 2-3 leaf stage, each filled with loam-compost- organic manure soil (3:1:1). Plants were divided into two groups. (a) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The zinc oxide (ZnO) NPs at a concentration of 100 mg L –1 significantly increased the leaf area, shoot and root dry weight, and chili plants fruit yield compared to the control group . A subsequent study illustrated that the application of Ag NPs to chili plant leaves, at a concentration of 50 mg L –1 , resulted in increased photosynthetic activity, growth, and yield, when the plants were subjected to drought-stress conditions …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The zinc oxide (ZnO) NPs at a concentration of 100 mg L –1 significantly increased the leaf area, shoot and root dry weight, and chili plants fruit yield compared to the control group . A subsequent study illustrated that the application of Ag NPs to chili plant leaves, at a concentration of 50 mg L –1 , resulted in increased photosynthetic activity, growth, and yield, when the plants were subjected to drought-stress conditions …”
Section: Resultsmentioning
confidence: 97%
“…21 A subsequent study illustrated that the application of Ag NPs to chili plant leaves, at a concentration of 50 mg L −1 , resulted in increased photosynthetic activity, growth, and yield, when the plants were subjected to drought-stress conditions. 56 3.5. Influence of NP Foliar Treatment on Phytochemical Constituents of the Chili Plant.…”
Section: Impact Of Foliar Nps On Chili Plant Growth Parametersmentioning
confidence: 99%
“…This may be related to the increased water and nutrient uptake of seeds treated with AgNPs. Mubashir et al [90] investigating the efficacy of nano-nutrient solutions (NNS) on growth and biochemical attributes of tomatoes under drought stress, reported that NNS administration resulted in more osmolyte production such as sugars and free amino acids, which may have contributed significantly to the maintenance of tissue water content. Osmolites, which have the ability to maintain the water potential gradient, have a significant effect on plant growth and productivity and have a protective effect in drought conditions [91,92].…”
Section: Discussionmentioning
confidence: 99%